Morphological characteristics and antioxidant activity of pollen silver birch (Betula pendula Ehrh.) - Tetiana, Shevtsova; Kateryna, Garkava; Jan, Brindza; Radovan, Ostrovsky (Pharmacognosy Communications)
Objective: In Ukraine, as well as in many other countries of the world, different parts of a birch is used in food, pharmacology and cosmetology for the purpose of health improvement. Contrary to this, birch pollen causes an allergy. The aim of this study is to document the morphological differences and antioxidant activity of pollen grains of a silver birch collected from different habitats in Ukraine, and to define the relationship between them. Materials and Methods: For the comparative analysis 7 samples of the silver birch pollen have been prepared taking into account different collection sites, background radiation and anthropogenic influence in Kyiv and Rivne regions of Ukraine. The length of polar axis, equatorial axis, apoporial field edge, shape index and other morphological traits were evaluated on scanning electron microscope. Total antioxidant activity of aqueous and ethanol extracts of birch pollen grains were defined in reaction with DPPH. Results: Variability of the most important morphological traits of pollen, the length of the polar and equatorial axis, was 17.9 μm (Pereyaslav-Khmelnytsky (control)) – 18.9 μm (Ivankiv) and 22.6 μm (Pereyaslav-Khmelnytsky (control)) – 23.9 μm (Ivankiv) respectively. The shape index ranged from 0.77 (Kuznetsovsk) to 0.81 (Pereyaslav-Khmelnytsky). It was established that silver birch pollen is characterized by high antioxidant activity. A measured value of total antioxidant activity (TAA) for aqueous pollen extracts was between 80.5% (Pereyaslav-Khmelnytsky (control)) and 85.5% (Ivankiv). For the ethanolic extracts it was quantified between 60.3% (Hotsky (control)) and 84.9% (Kuznetsovsk). Statistically significant differences between birch pollen samples from different habitats in Ukraine were found in all researches. Conclusions: Our results have confirmed that there are distinctions between populations of Betula pendula Roth. in morphological traits and antioxidant activity of pollen grains, and also in the other evaluated traits.
Keywords: silver birch; Betula pendula Roth.; syn. B. verrucosa Ehrh.; pollen; morphology; total antioxidant activity